2012
DOI: 10.1021/la204841n
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for a Density Distribution: Particle Size Analysis of Core–Shell Nanocomposite Particles Using Disk Centrifuge Photosedimentometry

Abstract: Abstract. Many types of colloidal particles possess a core-shell morphology. In this paper we show that, if the core and shell densities differ, this morphology leads to an inherent density distribution for particles of finite polydispersity. If the shell is denser than the core, this density distribution implies an artificial narrowing of the particle size distribution as determined by disk centrifuge photosedimentometry (DCP). In the specific case of polystyrene/silica nanocomposite particles, which consist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 60 publications
1
45
0
Order By: Relevance
“…A detailed discussion and in-depth analysis of these techniques fall out of the scope for this review although excellent literature material and technical notes are available [97][98][99]. In short, these techniques utilize high centrifugal force to deposit NPs in fractions based on density.…”
Section: Particle Size Determination By Sedimentation (X-ray Disc Cenmentioning
confidence: 99%
“…A detailed discussion and in-depth analysis of these techniques fall out of the scope for this review although excellent literature material and technical notes are available [97][98][99]. In short, these techniques utilize high centrifugal force to deposit NPs in fractions based on density.…”
Section: Particle Size Determination By Sedimentation (X-ray Disc Cenmentioning
confidence: 99%
“…Due to this separation capability, DCS is able to better distinguish the signals arising from different particle sizes, whereas in a DLS system, the signal from larger particles often masks that of their smaller counterparts . One of the limitations associated with DCS is the need to have accurate density information (Bell, Minelli, Tompkins, Stevens, & Shard, 2012), which becomes increasingly challenging if particles are not pristine, e.g., due to the presence of adsorbed species on the surface of the particles (Fielding et al, 2012;Neumann et al, 2013). Recently, methods have been developed to correct density information in such cases, but this correction is only possible if certain assumptions are made, such as the amount of adsorbed species.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that the weight-average diameter reported by DCP for core-shell polystyrene/silica 20 nanocomposite particles is subject to a sizing artefact due to their inherent density distribution, which in principle can be reanalysed and corrected. 53 However, no such correction was applied in the present work. Hence the DCP standard deviation should be treated as an underestimate of the true width of the particle size 25 distribution.…”
Section: Disc Centrifuge Photosedimentometry (Dcp)mentioning
confidence: 95%